Türkçe'de soru - Altun, Hilal Oytun (My University, 2009)
This thesis analises interrogative sentences in Turkic languages both semantically and sentactically. Historical eras of the Turkic languages; Old Turkic, Karahanid, Kharezm, Kipchak, Chagatay, Old Anatolian Turkish, Ottoman Turkic languages and the modern Turkic languages; Altai, Azeri, Bashkir, Chuvash, Gagauz, Karachay-Balkar, Karakalpak, Kumyk, Nogai, Sakha/ Yakut, Kazakh, Kyrgyz, Tatar, Turkmen, Uyghur, Uzbek and Turkish languages were examined in this study. The texts written in Turkic languages were scanned to find interrogative sentences, and the examples have been given with their Turkish translations. First chapter of the thesis consists of two parts: yes-no questions and whquestions. In this chapter the place of question particle in the sentence, and the interrogative sentences made via intonation were examined. In the second part of the first chapter the interrogative words were categoryzed according to their functions in the sentences. In the second chapter types of rhetorical questions were analysed. Interrogative sentences can be divided two gropus according to their fınctions: First was “real” interrogative sentences which their function is mainly to have information and these sentences require answer. The second type is “rhetorically interrogative” which doesn’t require any answer. It has three types: 1. Practical questions, 2. Exclamatory questions, 3. Rhetorical questions. Third chapter focuses on the secondary elemets of interrogative sentences which are interjections and question mark. At the glossary part of the thesis the interrogative determiners and interjections were listed. In this glossary it is possible to follow morphologic changes of the common interrogative words in the Turkic languages. At the end of this thesis there’s a conclusion part and the bibliography. Key words: Interrogative sentences, Interrogative particle, Interrogative determiners, Interrogative interjections, Question mark, Rhetorical questions, Turkic languages, Comparative grammar, Morphology, Syntax.
Keywords: Türk Dili; Türkçe